2016
DOI: 10.1093/alcalc/agw077
|View full text |Cite
|
Sign up to set email alerts
|

Nerve Growth Factor Protects Against Alcohol-Induced Neurotoxicity in PC12 Cells via PI3K/Akt/mTOR Pathway

Abstract: In this study, we chose the PC12 cell line as a neuronal model, and our results demonstrate that nerve growth factor can induce autophagy with the neuroprotective effect and regulatory mechanisms of alcohol-induced autophagy in PC12 cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 40 publications
1
16
0
1
Order By: Relevance
“…It is widely known that PI3K/AKT and MAPK/ERK pathways are two major intracellular signaling networks activated by growth factors responsible for the cell survival [18]. It has been reported that NGF mediated neuroprotective signaling is most likely to depend on PI3K/AKT rather than MAPK/ERK pathway [19][20][21]. The results obtained in the current study indicate that selective activation of PI3K/AKT by NGF mimetic is sufficient for the manifestation of neuroprotective activity in vivo.…”
Section: Resultssupporting
confidence: 61%
“…It is widely known that PI3K/AKT and MAPK/ERK pathways are two major intracellular signaling networks activated by growth factors responsible for the cell survival [18]. It has been reported that NGF mediated neuroprotective signaling is most likely to depend on PI3K/AKT rather than MAPK/ERK pathway [19][20][21]. The results obtained in the current study indicate that selective activation of PI3K/AKT by NGF mimetic is sufficient for the manifestation of neuroprotective activity in vivo.…”
Section: Resultssupporting
confidence: 61%
“…PI3K/Akt cascade seems to provide trophic support for neurons, block apoptosis, facilitate signal transmission and mediate cell growth and differentiation in neurons. Also, it is reported that NGF is mediated by PI3K/Akt/mTOR pathway [281][282][283]. Ras-ERK pathway is a key promoter of neurite outgrowth and also has been found to enhance axonal survival [284].…”
Section: Pharmacological Agentsmentioning
confidence: 99%
“…This anti-apoptotic effect of NGF is consistent with previous studies and may improve recovery following SCI. 48,49 Functional recovery is an essential factor for successful SCI treatment. In this study, locomotor function was assessed in rats after SCI.…”
mentioning
confidence: 99%